Green synthesis of multifunctional MgO@AgO/Ag2O nanocomposite for photocatalytic degradation of methylene blue and toluidine blue - Younes Zidane; Younes Zidane; Salah E. Laouini; Salah E. Laouini; Abderrhmane Bouafia; Abderrhmane Bouafia; Souhaila Meneceur; Souhaila Meneceur; Mohammed L. Tedjani; Mohammed L. Tedjani; Sohad A. Alshareef; Hanadi A. Almukhlifi; et al. (Frontiers in Chemistry, 2022)
Introduction: In this paper, MgO@AgO/Ag2O nanoparticles were greenly synthesized, the current idea is to replace the harmful chemical technique with an ecofriendly synthesis of metal oxide nanoparticles (NPs) utilizing biogenic sources.Methods: The current investigation was conducted to create silver oxide NPs decorated by MgO NPs (namely, MgO@AgO/Ag2O nanocom-posite) using the leaves extract of Purslane (Portulaca Oleracea) as the reducing and capping agent. The nanopowder was investigated by means of X-ray diffraction, scanning electron mi-croscope, BET surface area, Fourier transform infrared, and UV-vis spectrophotom-eter studies. XRD studies reveal the monophasic nature of these highly crystalline silver nano-particles. SEM studies the shape and morphology of the synthesis AgO/Ag2O and MgO@AgO/Ag2O NPs. The presence of magnesium and oxygen was further confirmed by EDS profile.Results and discussion: The surface area was found to be 9.1787 m2/g and 7.7166 m2/g, respectively. FTIR analysis showed the presence of specific functional groups. UV-vis spectrophotometer studies show the absorption band at 450 nm due to surface plasmon resonance. The results have also indicated the high performance of the greenly synthesized AgO/Ag2O NPs and MgO@AgO/Ag2O NPs for photocatalytic activity dye degradation (methylene blue and toluidine blue).